Gender at Work : A Companion to the World Development Report on Jobs - World Bank (Washington, DC, 2014)
Today, many more girls are going to school and living longer, healthier lives than 30 or even 10 years ago. That was the good news in our flagship 2012 World Development Report on gender. But this has not translated into broader gains. Too many women still lack basic freedoms and opportunities and face huge inequalities in the world of work. Globally, fewer than half of women have jobs, compared with almost four-fifths of men. Girls and women still learn less, earn less, and have far fewer assets and opportunities. They farm smaller plots, work in less profitable sectors, and face discriminatory laws and norms that constrain their time and choices, as well as their ability to own or inherit property, open a bank account, or take out a loan—to buy fertilizer, for example, that would boost food production for whole communities. Gender at Work looks closely at existing constraints as well as policies and practices that show promise in closing the gaps. A companion to the 2013 World Development Report on jobs, the report advocates investing more in women’s capabilities and eliminating structural barriers such as laws that bar women from owning property, accessing financing, or working without permission from a male relative.